Advances in the diagnosis of sickle cell retinopathy. (3rd September 2018) - Mathew, Raeba; Sivaprasad, Sobha
ABSTRACT: Introduction : Sickle cell disease (SCD) is an occlusive vascular disease that affects the vasculature of any part of the body including retina. Although the proliferative form of sickle cell retinopathy (SCR) may be more potentially damaging leading to visual impairment, non-proliferative forms too manifest changes in macula and peripheral retina. Advances in management of systemic complications of SCD have improved patient survival into adulthood with better quality of life leading to increased frequency of all ocular complications. Hence regular screening and early diagnosis of SCR is important to forestall visually significant complications of the same. Areas covered : This article gives a review of recent advances in structural and functional diagnostic imaging modalities such as spectral domain optical coherence tomography (OCT), wide-field retinal fundus photography/angiography, OCT angiography, microperimetry, electroretinography, and multimodal imaging in assessment of SCR. A literature search was conducted on PubMed on diagnostic modalities in SCR. Considering rarity of the condition, large population studies are not available therefore articles on small studies and case series are also included. Expert opinion : Multimodal imaging allows a comprehensive evaluation of the central and peripheral features of SCR. This helps in early diagnosis of complications and timely intervention for effective management.